Management of tinnitus in English NHS audiology departments: an evaluation of current practice - Hoare, Derek J.; Gander, Phillip E; Collins, Luke C.; Smith, Sandra; Hall, Deborah A. (Wiley, 2010)
Rationale, aim and objective: In 2009, the UK Department of Health formalized recommended National Health Service practices for the management of tinnitus from primary care onwards. It is timely therefore to evaluate the perceived practicality, utility and impact of those guidelines in the context of current practice. Methods: We surveyed current practice by posting a 36-item questionnaire to all audiology and hearing therapy staff that we were able to identify as being involved in tinnitus patient care in England. Results: In total, 138 out of 351 clinicians responded (39% response rate). The findings indicate a consensus opinion that management should be tailored to individual symptom profiles but that there is little standardization of assessment procedures or tools in use. Conclusions: While the lack of standardized practice might provide flexibility to meet local demand, it has drawbacks. It makes it difficult to ascertain key standards of best practice, it complicates the process of clinical audit, it implies unequal patient access to care, and it limits the implementation of translational research outcomes. We recommend that core elements of practice should be standardized, including use of a validated tinnitus questionnaires and an agreed pathway for decision making to better understand the rationale for management strategies offered.